Empowering Outpatients to Use Mobile JKN for Queue Registration at RSUD Bangil - Nur Hamid Abdullah; Alya Nurryta Putri; Fita Rusdian Ikawati; Lilik Afifah; Dewi Anggih Surya Permatasari; Elsa Andara Dita Amellia; Shevia Dwi Nugraheni; Widya Lailatur Rofida; Syahfira Nur Jannah; Immaculata Vettha Sarasvati Widasari; Erva Mar’atul Mahmudah (AMK : Abdi Masyarakat UIKA, 2025)
Mobile JKN is a digital platform launched by BPJS Health to simplify access to healthcare services, particularly through its online queue registration feature. Despite its benefits, many users still struggle to operate the application due to limited digital literacy. This community service program aimed to enhance public competency in utilizing the Mobile JKN app for outpatient registration at RSUD Bangil. The activity involved direct health education, live app demonstrations, and personal guidance for patients and their families. Effectiveness was evaluated through pre- and post-activity questionnaires measuring knowledge improvement. The results indicated a significant increase in participants’ ability to independently use the online queue function. This initiative is expected to contribute to digital transformation in healthcare services and improve the efficiency of outpatient registration procedures.